PENGARUH DAYA DAN DURASI OPERASI REAKTOR TERHADAP KONSENTRASI 3H DAN 14C DI AIR SISTEM PENDINGIN PRIMER REAKTOR RSG-GAS - Udiyani, Pande Made; Subiharto; L., Nugroho (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
The influence of reactor power and operation duration on concentration of 3H and 14C in primary coolant water system RSG-GAS reactor has been studied. The existence of nuclides 3H and 14C in primary coolant system RSG-GAS reactor is a result of fission product and activation. These nuclides have potential internal and external radiation hazard, due to long half life i.e. 12,26 years and 5568 years for 3H and 14C respectively, so that will have significant radiological impact. Analysis and water sample measurement of the primary coolant system has been done by using LSC (Liquid Scintillation Counter). The objective of this research is to study the influence of reactor power and its operation duration to 3H and 14C concentration in coolant system, the correlation of these nuclide concentration with reactor system related to the component ageing, and estimation of receiving RSG-GAS reactor worker radiation for safety in working area and personnel safety. The results showed that 3H and 14C concentration in RSG-GAS reactor are proportional to the reactor power and its operation time duration. The fast increasing of 3H and 14C concentration in RSG-GAS reactor primary coolant system after the first five years operation might be caused by high intensity of reactor operation, and the accumulation of long half life nuclides. The results of this research can be used to study the reactor operation safety, personnel and working area safety, and also to study the reactor ageing process.